PENGARUH LEADER MEMBER EXCHANGE (LMX) DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI MEDIASI (Studi pada Pegawai di Politeknik Ilmu Pelayaran Semarang) - Suryadi, Awel; Priyono, Bambang Suko (Jurnal Ilmiah Telaah Manajemen, 2017)
Target of this research to test and analyse Leader Member Exchange Influence ( LMX) And work characteristic to officer performance with mediation motivate Politeknik Ilmu Pelayaran Semarang. In this research of population of Officer Politeknik Ilmu Pelayaran Semarang amounting to 190 people. Intake of sample with sampling random stratified proporsional technique. Determination of is amount of sample use Slovin formula obtained by counted 129 responder. Data analysis use doubled linear regresi analysis. Pursuant to result of research can know by Leader Member Exchange (LMX) And work characteristic have an effect on positive and significant to motivation. Leader Member Exchange (LMX) And work characteristic have an effect on positive and significant to officer performance. Motivation have an effect on positive and significant to officer performance. Media influence motivation Leader Member Exchange (LMX) And work characteristic to officer performance of Politeknik Ilmu Pelayaran Semarang. Keywords: Leader Member Exchange (LMX), work characteristic, officer performance and motivation.